TESTING AND DIAGNOSIS OF DISTRIBUTED DIGITAL SYSTEMS - Hahanov, Vladimir; Yeliseev, Vladimir; Parfenty, Alexander (International Journal of Computing, 2014)
The complex system can be represented as hierarchy of simpler components. On the one hand different levels of hierarchy have an advantage for more deeply research of properties of the complex system. On the other hand a flexible model and method of testing and diagnosing of the complex system need to be developed. Moreover, international IEEE testability standards should be applied.The research presented in the current paper offers approach of testing of complex digital system based on hierarchy scaling during diagnosis experiment. Several models of testing are proposed. Main principles of testing system organization are given. The result of the work is significant time reduction of test and diagnostic of system overall.